The Importance of Awareness and Prevention of Suicide Trends in Youth - Pratama, Yanasta Yudo; Ayu Dewi Mahila, Niufti; Luthfi Adnan, Muhammad; Sameeh Abd El Qader AbuHilail, Hamza (Epidemiology and Society Health Review (ESHR), 2024)
Suicide is an incident that is a severe problem in society which is currently widespread. Suicide is the act of ending one's own life by using several techniques, such as hanging, making an incision in a blood vessel, or crashing into a moving vehicle such as a train or motorbike. Based on data from the World Health Organization (WHO), as many as 703,000 people committed suicide, with variations in suicide rates in various countries between 2 and 80 suicide deaths per 100,000 population. Men have a suicide rate that is up to 2.3 times higher than women. The majority of deaths due to suicide are more significant in low- and middle-income countries (LMICs), up to more than 70%